Legitimasi Sakral Dalang Dalam Ruwatan Sapuh Leger Di Pura Siwa Manik Dalang Buleleng - Ni Made Budi Yasmini; I Nyoman Suka Ardiyasa; I Putu Mardika (Jayapangus Press, 2026)
This research examines the sacred legitimacy of dalang in the Sapuh Leger purification ritual at Pura Siwa Manik Dalang, Buleleng, Bali. The study departs from the distinctive position of dalang in Balinese Hindu ritual practice, not merely as a performing artist but as a sacred mediator whose authority determines the validity of purification. This research aims to analyze the foundations of sacred legitimacy, the ritual relationship between Dalang Pengempon Pura and dalang ngayah, and its implications for the continuity of Sapuh Leger. Using a qualitative descriptive-narrative method with religious and cultural approaches, data were collected through observation, in-depth interviews, textual study, and documentation involving dalang, temple caretakers, religious figures, and ritual participants. The findings show that sacred legitimacy is constructed through lineage, mastery of ritual knowledge, competence in mantras and sacred texts, socio-religious recognition, and institutional involvement in the temple structure. The relationship between Dalang Pengempon Pura and dalang ngayah reflects a structured ritual authority based on hierarchy, devotion, and collective responsibility. Theoretically, this study contributes to the understanding of sacred authority as a form of legitimacy that is socially and ritually reproduced. Culturally, it affirms the role of dalang in preserving ritual knowledge, maintaining the validity of Sapuh Leger, and sustaining Balinese Hindu religious identity.